PENGARUH VIRAL MARKETING TERHADAP KEPERCAYAAN KONSUMEN DAN DAMPAKNYA TERHADAP KEPUTUSAN PEMBELIAN: (Studi Kasus Pada Produk Kecantikan Emina di Indonesia) - Zulfa Fauziyah; Dhany Isnaeni Darmawan (Universitas Serang Raya, 2024)
Problem: There is a problem of consumer trust in Emina beauty products in Indonesia which is influenced by Viral Marketing and knowing the extent of the influence of purchasing decisions that interfere with consumer trust Objective: This research aims to determine the influence of viral marketing on purchasing decisions with consumer trust as an intervening variable Methodology: This type of research is quantitative and uses descriptive analysis methods. The data analysis technique used is path analysis. The number of samples taken in this study used the Lemeshow formula (Lemeshow et al., 1997), this is because the population size is unknown or infinite. The sample used in this research was 98 respondents who were aware of Emina's Instagram social media, and had purchased and consumed Emina using purposive sampling. In this research, data collection techniques using questionnaires were used and analyzed using path analysis Research Findings/Results: This research is (1) Viral Marketing has a significant effect on Consumer Trust with a value of 10.890, Viral Marketing has a significant effect on Purchasing Decisions with a value of 8.137, (3) Consumer Trust has a significant effect on Purchasing Decisions with a value of 3.555 and (4) Consumer trust is unable to mediate viral marketing on purchasing decisions with a Z value of 1.389. Research Type: Market Research